2011
DOI: 10.1007/s11749-011-0244-4
|View full text |Cite
|
Sign up to set email alerts
|

On Hölder fields clustering

Abstract: In this paper, we study the k-means clustering scheme based on the observations of a phenomenon modelled by a sequence of random fields X 1 , · · · , X n taking values in a Hilbert space. In the k-means algorithm, clustering is performed by computing a Voronoi partition associated with centers that minimize an empirical criterion, called distorsion. The performance of the method is evaluated by comparing a theoretical distorsion of empirically optimal centers to the theoretical optimal distorsion. Our first re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…For instance Biau et al (2008) prove that in a separable Hilbert space, and provided |X | ≤ L almost surely, then ER(ĉ) − R ≤ 12kL 2 / n, for all n ≥ 1. A similar result is established in Cadre and Paris (2012) relaxing the hypothesis of bounded support by supposing only the existence of an exponential moment for X . In the context of a separable Hilbert space, Levrard (2015) establishes a stronger result under some conditions involving the quantity p(t ) defined as follows.…”
Section: Risk Boundssupporting
confidence: 62%
“…For instance Biau et al (2008) prove that in a separable Hilbert space, and provided |X | ≤ L almost surely, then ER(ĉ) − R ≤ 12kL 2 / n, for all n ≥ 1. A similar result is established in Cadre and Paris (2012) relaxing the hypothesis of bounded support by supposing only the existence of an exponential moment for X . In the context of a separable Hilbert space, Levrard (2015) establishes a stronger result under some conditions involving the quantity p(t ) defined as follows.…”
Section: Risk Boundssupporting
confidence: 62%
“…By means of the Kappa coefficient of agreement, it is shown that if the data are sampled at regular time intervals the functional nature of the data can be ignored without damaging the performance of the clustering procedure. This is a numerical validation of the theoretical result of [5]. A numerical counter-example has been included, with a non-uniform discretization strategy, for raw-data clustering methods in which the performance of aKKm and the K-means algorithm is significantly deteriorated compared with the KK-means algorithm, which accounts for the functional nature.…”
Section: Introductionmentioning
confidence: 92%
“…The K-means algorithm works well for uniformly spaced functional data (see [5]). In our case, this is shown in Table 5 where the K-means algorithm gives κ values similar to those obtained with methods based on projections on RKHS in all the test problems with uniformly spaced data.…”
Section: P-kk-meansmentioning
confidence: 99%
See 1 more Smart Citation
“…The question of general unbounded distributions is more challenging and has been studied less. The case where the vectors X i have well behaved exponential moments was analyzed in (Cadre and Paris, 2012). Results under less restrictive assumptions include: the uniform deviation bounds in (Telgarsky and Dasgupta, 2013;Bachem, Lucic, Hassani and Krause, 2017); a sub-Gaussian excess distortion bound in (Brownlees, Joly and Lugosi, 2015) for the so-called k-medians problem; and the results for trimmed quantizers in (Brécheteau, Fischer and Levrard, 2018).…”
Section: Introductionmentioning
confidence: 99%